Combination therapy of Fludarabine and Cyclophosphamide(FC) Combination Regimen in advance stage of Chronic Lymphocytic Leukemia - Matti, Bassam F.; Naji, Alaadin S.; Majid, Amar F.; Sabir, Shahlaa’ F.; Alwan, Alaa F. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: the exposure of  chronic lymphocytic leukemia (CLL) cells to fludarabine and cyclophosphamide resulted in an increased, synergistic cytotoxicity . DNA repair mechanisms in CLL cells, which are initiated in response to cyclophosphamide exposition, are inhibited by fludarabine. This observation was later translated into clinical trials evaluating the combination of fludarabine plus cyclophosphamide (FC) showed promising efficacy with response rates exceeding 90% in previously untreated and pretreated patientAim of  this study: To assess the efficacy and safety of combination therapy of fludarabine plus cyclophosphamide in  Iraqi adults patients with advance stage of chronic lymphocytic leukemia (CLL) in both previously treated and untreated patients and to assess the treatment free  and  overall survival in CLL patient who are receiving FC regimen therapy.Patients and methods: Single arm study was done between February 2005 and fabruary2009.This study included 64 Iraqi patients aged between 39-77years old with advanced stage CLL .All patients  received FC combination Therapy(fludarabine25mg/m2 plus cyclophosphamide 250mg/m2 for 3 days intravenously, repeated every 28 days). Treatment was administered for 4-6 courses. Forty eight(75%) patients were treatment naive(N) and 16(25%)were previously treated(Y) with alkylating agent.Results: This combination chemotherapy resulted in 39.1% complete remission rate(CR) and 39.1%partial remission(PR) rate with overall response rated78.2%.The  2years median treatment-free survival was 90% with the median duration of response was 18months. Also  there was a significant difference(p value